Vocabulary Size and Academic Essay Writing: A Correlational Study among EFL Students Using VST - Amel, Firda Amelia; Endah Nur Tjendani; Fatih Al fauzi (Journey: Journal of English Language and Pedagogy, 2026)
This study revisits the widely accepted claim that vocabulary knowledge is associated with writing ability by questioning how far vocabulary size, when measured through a standardized instrument, actually explains variation in academic writing performance. While many previous studies have simply confirmed the presence of a positive correlation, they often treat vocabulary as a broad construct and overlook the need to link specific lexical measures to writing outcomes, which leaves a gap in how this relationship is conceptually understood. To address this, a quantitative correlational design was employed involving 30 EFL students from different semesters at the Islamic University of Jember (2024/2025), selected through stratified random sampling. Vocabulary size was measured using the Vocabulary Size Test (VST), and writing performance was assessed through an academic essay task using Widodo’s rubric. The results show a moderate but meaningful correlation (r = 0.569, p < 0.05), indicating that vocabulary size contributes to writing quality, yet does not function as a dominant or isolated predictor. This finding challenges overly deterministic views of lexical competence and suggests that academic writing development is shaped by multiple interacting factors, with vocabulary size acting as one important, but limited, component..